Clinical Context and Detection of the Murmur of Advanced Aortic Stenosis. Issue 4 (April 2018) - Kattoor, Ajoe John; Shanbhag, Anusha; Abraham, Annette; Vallurupalli, Srikanth
Abstract : Objectives: Auscultation is an important clue to the presence of aortic stenosis (AS). We sought to assess the effect of symptom status, prior knowledge of diagnosis, and other patient factors on murmur detection. Methods: Patients with moderate-to-severe AS by echocardiography at a single center between June 2015 and June 2016 were included. Five consecutive patient encounters (inpatient and outpatient) within 12 months before the echocardiogram were analyzed. Results: Ninety-five patients (418 different clinician encounters) were studied. The murmur of AS was identified by only 39% of clinicians. In multivariate analysis, significant determinants of murmur detection were examination in outpatient setting (odds ratio [OR] 3.40, 95% confidence interval [CI] 1.75–6.61), known history of AS (OR 2.77, 95% CI 1.53–5.01), female sex (OR 1.97, 95% CI 1.07–3.60), and presence of symptoms (OR 1.91 95% CI 1.12–3.26). Compared with the murmur detection findings by clinicians in medicine, the findings of surgical specialty clinicians were significantly lower (OR 0.12, 95% CI 0.06–0.26, P < 0.001). Conclusions: In this real-world assessment, clinical context played an important role in the auscultation of AS murmur. The findings have important implications for the clinical diagnosis of asymptomatic advanced AS. Abstract : Auscultation provides the initial diagnostic clue to the presence of aortic stenosis. A real-world assessment of the effect of various patient characteristics on the detection of murmur was performed in echocardiographically confirmed moderate-to-severe aortic stenosis. In this retrospective study, murmur of aortic stenosis was more likely to be undetected in asymptomatic patients and in the inpatient setting. This is the first time the effect of clinical context on cardiac auscultation has been investigated in a real-world setting. These data have important implications in the early diagnosis of aortic stenosis and in guiding medical training programs.